Resistance of Lima Bean (Phaseolus lunatus L.) to the Red Spider Mite Tetranychus neocaledonicus (Acari: Tetranychidae) - França, Solange Maria de; Silva, Paulo Roberto Ramalho; Gomes-Neto, Antonio Vieira; Gomes, Regina Lucia Ferreira; da Silva Melo, José Wagner; Breda, Mariana Oliveira (Frontiers in Plant Science, 2018)
The red spider mite, Tetranychus neocaledonicus (Acari: Tetranychidae) can be an important pest on lima bean (Phaseolus lunatus L.). Thus, the objective of this work was to assess the antibiosis and antixenosis effects of lima bean genotypes on T. neocaledonicus, through the evaluation of performance parameters as well as the host preference for food and oviposition. Nine lima bean genotypes from the Active Bank of Germplasm of the Federal University of Piauí – BGP / UFPI were screened. To assess antibiosis parameters, eggs of T. neocaledonicus were individually placed on leaf disks of each genotype. The period and survival of the different stages of development (larvae, protonymph, deutonymph and adult), pre-oviposition, oviposition and post-oviposition period, longevity and fecundity of females were evaluated, and fertility life table parameters were calculated. In choice tests, adult females of T. neocaledonicus were used. The numbers of mites and eggs were counted for each genotype. The protonymph, egg-adult, longevity and oviposition period, fertility life table parameters, as well as the food and oviposition preference were affected by lima bean genotypes. We found that some genotypes reduced adult female longevity, increased the larval and egg-adult period, decreased oviposition period, negatively affected the fertility life table parameters, reducing the net reproductive rate (Ro), the intrinsic rate of increase (rm) and the finite rate of increase (λ), while increasing the population doubling time (DT), exhibiting a reliable antibiosis effect upon T. neocaledonicus. Nevertheless, these same genotypes were the most preferred for food and oviposition. By contrast, some other genotypes reduced the adult female longevity and oviposition period, elongated the larval period and affected fertility life table parameters, demonstrating an antibiosis effect upon T. neocaledonicus. Moreover, these other genotypes were among the less preferred for food and oviposition, exhibiting an additional antixenosis effect. Thus, our results demonstrate that the genotypes of lima bean may present distinct levels of resistance to T. neocaledonicus, and this resistance may be an important tool for Integrated Pest Management. This is one of the first studies aiming to describe mite resistance sources in lima bean.